Temperature effects on grain growth phenomena and magnetic properties of silicon steels used in marine applications - Nikolaos D Papadopoulos; Polyxeni Vourna; Nikos Stefanakis; Sotirios Xafakis; Evangelos Hristoforou (Annals of Marine Science - Peertechz Publications, 2023)
The present paper investigates the stages of the microstructure and texture evolution in non-oriented electrical silicon steels by means of magnetic measurements and metallographic analysis. The goal of this work was to study temperature effects and their influence on grain growth processes in non-oriented electrical steels while being subjected to different annealing conditions and to clarify the mechanism of grain boundary motion during annealing. It is important to study the development of texture and grain size in electrical steel samples along the entire production line chain (hot rolling, cold rolling, and final annealing), as both are affected by each processing stage. The lack of magnetic data dependent on the operating temperature of non-oriented electrical steels makes it impossible to accurately design high-power motors (e.g., propulsion systems in ships) or generators that are to operate at high temperatures. The correlation of magnetic properties with the microstructure of electrical steels can yield important information about their suitability for various substrates and marine applications. In addition, it can potentially non-destructively define both the annealing stage and the preferred crystallographic growth pattern in single-phase ferritic steels, which affect the performance and longevity of the electromagnetic devices in which these are used.